PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING “THINK TALK WRITE” DALAM MENULIS CERITA FANTASI PESERTA DIDIK KELAS VII-F SMPN 1 WONOAYU SIDOARJO - Riski Vidiyanti; Tri Indrayanti (Universitas PGRI Adi Buana Surabaya, 2019)
The purpose of this study is that students are able to write fantasy stories through the Think Talk Write learning model. The researcher applies a Think Talk Write learning model that is applied to students of class VII-F Wonoayu Sidoarjo 1 Junior High School. Researchers use the application of learning models, namely learning Think Talk Write. This learning model helps students to get maximum learning outcomes in groups so as to foster a sense of family and cooperation. Learning to write fantasy stories was chosen as the study material because it had not yet achieved the ability of students to write fantasy stories. This is based on learning outcomes that have not yet reached the expected KKM.